Research on the Influence of Axle Deviation Angle on Riding Performance of Autonomous-Rail Rapid Trams - YU Juan; ZHOU Sheng; PENG Jing; LIU Xiaocong (Kongzhi Yu Xinxi Jishu)
This paper explores the issue of axle deviation caused by the accuracy deterioration of steering angle sensors on autonomous-rail rapid trams (ART), focusing specifically on its effects on vehicle operating postures. Based on vehicle dynamics modeling, the study investigated the impact of axle deviation on vehicle riding performance, through lateral dynamics analysis and calculations. Multi-body system dynamics simulations were conducted to verify the reliability of the calculation results, further revealing the correlations between different axle deviation angles and changes in vehicle operating postures. Research results indicated that emerging axle deflection angles caused ARTs to operate in a skewed posture during straight running, and the steering angle and articulation angle of each axle were found to be linearly correlated with the axle deflection angles. In addition, compared to single-axle deflection angles, the coupling of multi-axle deflection angles displayed a superposition characteristic in vehicle appearance features, which facilitates the positioning analysis of faults in steering angle sensors. This paper also proposes suggestions on the diagnosis method of faults related to accuracy degradation suffered by steering angle sensors on ARTs, along with effective measures to improve the safety and reliability of ART operation.